Just a minute : a trickster tale and counting book - Morales, Yuyi (Chronicle Books, 2003)
In this version of a traditional tale, Senor Calavera arrives at Grandma Beetle's door, ready to take her to the next life, but after helping her count, in English and Spanish, as she makes her birthday preparations, he changes his mind.